Optimum Radiological Screening Examination for Lumbar Spine - Roya Etemad-Rezai (McGill Journal of Medicine, 2020)
A retrospective study was performed to assess the diagnostic contribution of oblique view films of the lumbar spine, to information obtained from anteroposterior (AP) and lateral films, as an initial screening tool for the detection of pars interarticularis defects. Twenty-two cases of lumbar spondylolysis were selected from 243 lumbar spine reports, randomly combined with 40 plain X-rays of normal lumbar spines, and evaluated by radiology residents. The frequency of correctly detecting a pars defect on lateral vs. right and left oblique views was determined. Of the bilateral spondylolyses, 85% were diagnosed on lateral films compared to 35% on oblique radiographs. Both views gave poor diagnostic yield in detecting unilateral pars defects. In evaluating a total of 186 X-rays, an average of 31 oblique films were incorrectly diagnosed, as compared to an average of 14 misdiagnosed lateral films. Considering the low sensitivity associated with the use of oblique view radiography, in addition to the extra cost and significantly increased radiation exposure seen with this procedure, our findings indicate that oblique views should be used only for selected patients who might require further investigation. We therefore recommend that the initial lumbosacral radiological evaluation be limited to AP and lateral views.